Consumption of animal-source foods in Ethiopia: Patterns, changes, and determinants - Abegaz, Getachew Ahmed; Hassen, Ibrahim Worku; Minten, Bart (International Food Policy Research Institute, 2018)
Using unique nationally representative household consumption data sets that extend from 1995/96 to 2010/11, this study looks at patterns and changes in ASF (animal-source food) consumption and attempts to identify some of the drivers of these dynamics. We further assess future demand in overall ASF consumption as well as for commercial market development.